Introduction to agricultural economics - Penson, John B. (Upper Saddle River, N.J. : Pearson Prentice Hall, 2010)
Introduction to Agricultural Economics, Fifth Edition, provides a systematic introduction to the basic concepts and issues in economics as they relate to the food and fiber industry, a major segment of the U.S. economy.
Earlier editions entered under: Penson, John B.
Includes bibliographical references and index.
Keywords: Agriculture -- Economic aspects